Beyond Technical Success: Postoperative Systemic Deterioration and Timely Clinical Rescue in Minimally Invasive Abdominal Surgery - José Eduardo Vallejo Ramírez; Ana Carla Naranjo González; Angie Michelle Junco Aguaiza; Diego Clemente Moreno; David Eduardo Espinosa Ortiz; Pablo Eduardo Navarro López; Vicente Treviño Caballero; Justin Santiago Palacios Moreira; Aldo Bolivar Zavala Segovia (IECCMEXICO, 2026)
Minimally invasive abdominal surgery reduces surgical trauma and facilitates postoperative recovery; however, it does not eliminate the risk of systemic complications or progression to organ dysfunction. This study evaluated the frequency, early manifestations, severity, and multidisciplinary management of systemic complications following laparoscopic and robot-assisted abdominal procedures. A prospective observational cohort design was used, including 263 adult patients with follow-up from the immediate postoperative period through 30 days. Clinical, surgical, anesthetic, physiological, laboratory, and outcome variables were collected. Complications were classified using the Clavien–Dindo system, while early warning signs and multidisciplinary response times were documented. Overall, 83 patients (31.6%) developed at least one systemic complication. Respiratory complications were the most frequent (17.1%), followed by infectious (11.0%), cardiovascular (9.1%), renal (7.6%), metabolic (6.5%), neurological (4.9%), and thromboembolic events (2.7%). Among affected patients, tachycardia was the most common warning sign (71.1%), followed by tachypnea (54.2%) and a new or increased oxygen requirement (48.2%). Severe Clavien–Dindo Grade III–V complications occurred in 27 patients, representing 32.5% of affected patients and 10.3% of the complete cohort. Severe complications developed in 14.3% of patients receiving a multidisciplinary response within 60 minutes and in 58.8% of those with a delayed response. A response exceeding 60 minutes was associated with greater odds of severe complications (OR = 8.57; 95% CI: 2.99–24.54; p < .001), unplanned intensive care admission, and reintervention. These findings demonstrate that postoperative deterioration frequently presents through combined multisystem abnormalities. Structured surveillance, standardized escalation pathways, and timely multidisciplinary intervention are essential for preserving the benefits and safety of minimally invasive abdominal surgery.